Comparative morphological analysis of yellow-legged hornet (Vespa velutina nigrithorax) and European hornet (Vespa crabro) based on modern imaging techniques - Sipos, Tamás; Kolics, Balázs; Kolics-Horváth, Éva; Donkó, Tamás; Csóka, Ádám; Kozma-Bognár, Kristóf; Kovács, András; Farkas, Sándor; Somfalvi-Tóth, Katalin; Keszthelyi, Sándor (Frontiers in Ecology and Evolution, 2025)
IntroductionThe yellow-legged hornet (Vespa velutina nigrithorax Lepeletier, 1836) and the European hornet (Vespa crabro L., 1758) are two social generalist predator wasps that have successfully expanded beyond their native ranges, raising ecological concerns in newly colonized regions. This study presents a comparative analysis of the two species based on morphological parameters derived from digital microscopy and micro-CT imaging.MethodsSpecies were collected in Hungary and examined in order to assess differences in body size, colouration, and flight-related morphology. To determine the differences between species, 16 different morphological parameters were measured by micro-ct examination and digital microscopy. The flight parameters of the examined two species were assessed through 14 flight-related coefficients and a correlation matrix and a linear model based on these.Results and discussionResults from the colour analyses performed significantly darker colouration of V. v. nigrithorax compared with V. crabro. Morphological measurements confirmed that V. crabro is generally larger and more robust in body size, while V. v. nigrithorax posesses relatively longer legs and a greater wing surface area proportional to body mass. V. v. nigrithorax outperformed V. crabro in most flight-related traits, e.g. speed, manoeuvrability, balancing ability, hovering and carrying capacity. Correlation analyses supported these findings, showing stronger associations among wing parameters in V. v. nigrithorax and more uniform body-thorax interaction and more robust body structure in V. crabro. These results argue that V. v. nigrithorax’s better flight performance underlies its effective bee-hawking behaviour and competitive dominance in habitats in which the two hornet species co-occur. The study highlights how morphological adaptations contribute to predatory success and invasion potential. Our findings also confirm that in the absence of natural enemies, an adventive predator can exhibit significant ecological advantages in competitive interactions, certainly in the initial success of an invasive species.